2022
DOI: 10.1111/pace.14452
|View full text |Cite
|
Sign up to set email alerts
|

Result and technique consideration of radiofrequency catheter ablation of tachycardia in patients with dextrocardia

Abstract: Background: Patients with tachycardia, in the context of pre-existing dextrocardia, could benefit from catheter ablation. However, anatomical complexities hinder effective conduct of this procedure. We aimed to retrospectively summarize the clinical characteristics and the safety and efficiency, and recommended the technique considerations.Methods: Twenty-one cases from 19 patients with tachycardia and dextrocardia, who underwent catheter ablation between 2009 and 2021, were enrolled. All patients underwent ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Thus, the heart is located in the right of the chest, the apex of the heart points to the right, the aortic arch in the right of the chest, and the inferior vena cava are left-sided structures. Catheter ablation is an effective and safe strategy with a high success rate for managing patients suffering from WPW syndrome and dextrocardia ( 11 ). A previous study involving nine cases of patients with supraventricular tachycardia and dextrocardia showed that the successful rate of catheter ablation was 100% ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the heart is located in the right of the chest, the apex of the heart points to the right, the aortic arch in the right of the chest, and the inferior vena cava are left-sided structures. Catheter ablation is an effective and safe strategy with a high success rate for managing patients suffering from WPW syndrome and dextrocardia ( 11 ). A previous study involving nine cases of patients with supraventricular tachycardia and dextrocardia showed that the successful rate of catheter ablation was 100% ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are usually treated with antiarrhythmic medications and patients without adequate control are subjected to catheter ablation procedures (cryoablation or radiofrequency (RF) ablation). The feasibility of catheter ablation procedures for atrial fibrillation/flutter [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ], supraventricular tachycardia [ 101 , 102 , 103 ], including AVRT [ 101 ] and WPW syndrome [ 104 ], was demonstrated. Patients with an interrupted inferior vena cava should undergo the procedure using the jugular venous approach.…”
Section: Management Of Cardiac Malposition Patients During Adulthoodmentioning
confidence: 99%